The nationalist movement in the Levant during the nineteenth and early twentieth centuries - Mohammed, Assistant Professor Dr. Rahim Hassan (Thi Qar Arts Journal, 2023)
The idea of the emergence of the Arab nationalist movement is not accidental to the Arabs in terms of its general concept, as the Arab history has been filled with evidence and events that it is prominent in many roles, scenes and stages of the Arab era in previous historical periods. Therefore, there were several internal or external factors that contributed effectively to the crystallization and emergence of the nationalist, intellectual and literary currents and organizations, as the weakness of the authority of the Ottoman state, and what the Arab countries in general and the Levant in particular were exposed to, of colonial control, and opening the way for missionary missions in the cities of the Levant, had an impact on the Arab writers and thinkers in their interest in Arabic literature and reviving the Arabic language and the ancient Arab heritage. The Arab Renaissance, in its comprehensive concept, meant the transformation of the Arab society from a state of stagnation, backwardness and dependence in the Ottoman era, to a state of interaction and harmony with the political and civilizational developments, and the awareness of the Arab society of its national existence and its human role. Therefore, the ideas and calls of the Arab thinkers and reformers, especially in the Levant, called for the unification of the Arabs in a state independent of the Ottoman Caliphate, with a national entity unified in feeling, culture, goals and political, economic and military interests, and thus their efforts resulted in the establishment of nationalist, literary, scientific and political associations and parties, both inside and outside the Arab countries, and holding conferences to convey the voice of the sons of the Arab people to the public opinion in Paris, to demand their legitimate rights in achieving freedom, independence and getting rid of the dependence and tyranny of the Ottomans, as well as the European colonial countries, especially during and after the First World War.